Impact of Climate Variables on COVID-19 Pandemic in Asia: A Systematic Review - Saputra, Yoerdy Agusmal; Susanna, Dewi; Saki, Vernonia Yora (UI Scholars Hub, 2021)
COVID-19 has become a global pandemic and threatens public health systems worldwide. Virus transmission can be influenced by several factors, one ofwhich is climatic conditions. Temperature, humidity, precipitation, wind speed, and solar radiation play an important role in the transmission of infectious diseases and are variables that can determine the resistance of the SARS virus. This paper aimed to critically assess and provide evidence-based on the impactof climate variables on COVID-19 cases in Asia based on current knowledge to form the basis of guidelines for health care and prevention efforts. This systematic review used Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The articles were searched from ProQuest, Scopus,PubMed, and Springerlink databases. The reviewers had screened 2.784 abstracts, 103 full-text publications, and ultimately included 11 systematic reviews. The review found a consistently positive relationship between climate variables and COVID-19. Average temperature, maximum temperature, minimum temperature, and humidity (r = 0.83, 0.94, 0.93, 0.30) were significantly correlated with COVID-19 cases. Temperature, maximum humidity, and population density (adjusted R2 = 0.53, p<0.05), can be used as references in planning interventions during potential future pandemics. Linear regression framework, high humidity, and high temperature (p<0.05) significantly reduce the transmission of COVID-19. This systematic review shows that climate plays a role in the spread of the COVID-19 pandemic in Asia.